A comparison of mesophotic and shallow sponge holobionts resilience to predicted future temperature elevation - Raijman-Nagar, Lilach; Goren, Liron; Shefer, Sigal; Moskovich, Raz; Li, Zhiyong; Ilan, Micha (Frontiers in Marine Science, 2023)
Climate change is predicted to have detrimental impacts on sessile invertebrates, including sponges. Mesophotic ecosystems have been suggested to play a major role as refugia for coral reef sponge species, however knowledge regarding the ability of mesophotic sponges to cope with thermal stress is scarce. In this study we compared the response of the sponge Diacarnus erythraeanus, a widespread Red Sea sponge, from the shallow and mesophotic reef, to moderate and acute temperature elevation (2°C and 6°C, respectively) for short and long term periods (two and 35 days, respectively) by measuring physiological parameters (respiration, oxygen removal, pumping rates, and photosynthetic efficiency), and the microbiome composition change. The results indicated that mesophotic and shallow populations of D. erythraeanus are highly tolerant to both moderate and acute heat stress, demonstrating a high survival rate (100%) across the experimental treatments, with no visible signs of bleaching or necrosis. Exposure to heat stress resulted in significant alterations in the physiological parameters of sponges, including higher respiration rate and lower photosynthetic efficiency. These alterations were accompanied by correspondingly significant microbial adjustments, thus emphasizing the essential role of the microbiome in the host’s ability to persist when facing essential environmental stress. Moreover, while shallow and mesophotic sponges showed similar physiological tolerance to heat stress, their microbial response differed: while the microbiome diversity of the mesophotic sponges remained stable throughout the experiment, the shallow one significantly changed. This result suggests that their underlying coping mechanisms might differ between mesophotic and shallow populations. Since the associated-microbiome is largely regulated by the sponge-host genetics, difference in microbial adjustments to stress between populations, could indicate genetic variability between hosts. Therefore, while the results of this study support the hypothesis that mesophotic coral reefs could serve as thermal refugia for some sponge species, it raises the question regarding the validity of MCEs as a refuge for shallow populations. Finally, it emphasizes the crucial need to elucidate the underlying mechanisms governing the sponge-microbiome interactions, specifically in the context of the anticipated climate change scenarios.